Изучение устойчивости к вилту гибридов, полученных от интродуцированных сортов и форм хлопчатника - Мамедова, Н.Х.; Шихлинский, Г.М.; Гасанова, Г.И. (Фактори експериментальної еволюції організмів, 2013)
Aims. On artificial-infections background the phytopathological assessment of Verticillium wilt resistance was carried out in interspecific hybrids of cotton. Methods. Phytopathological used methods are tested for the first genereition (Fı) cotton hybrids. Results. Resistance assessment of interspecific cotton hybrids to Verticillium wilt showed that these were the best hybrids: 617-Т х Termez-7; 147-Ф х Todlo-16; Pima-5-1 x 3273; 5476-U x Мутант-487; Pima-S-4 x 18819; Antep x 159-F; S-2607 x kk-1543; AP-200 x S-5497; Acala-1517 BR x Antep. These hybrids were higher than 5 g., which was an indicator of high productivity. Conclusions. Experience of plant resistance to diseases shows that resistant varieties can be achieved by distant hybridization and they can be further tested for several years on a special background. Thus obtained interspecific hybrids can be used in the selection process as donors for this Verticillium wilt resistance in forming new resistant and tolerant cotton varieties.

Key words: Cotton, phytopathologi, resistance, hybrids, wilt.